The Association Between Metabolic Syndrome and Colorectal Cancer Risk by Obesity Status in Korean Women: A Nationwide Cohort Study - Seong-geun Moon; Boyoung Park (Korean Society for Preventive Medicine, 2022)
Objectives This study aimed to determine the association between metabolic syndrome (MetS) and the incidence of colorectal cancer (CRC) in Korean women with obesity. Methods Cancer-free women (n=6 142 486) aged 40-79 years, who underwent National Health Insurance Service health examinations in 2009 and 2010 were included. The incidence of CRC was followed until 2018. The hazard ratio (HR) of MetS for the incidence of colon and rectal cancer was analyzed according to body mass index (BMI) categories, adjusting for confounders such as women's reproductive factors. In addition, the heterogeneity of associations across BMI categories was assessed. Results Women with MetS were at increased risk of colon and rectal cancer compared to women without MetS (HR, 1.20; 95% confidence interval [CI], 1.16 to 1.23 and HR,1.15; 95% CI, 1.11 to 1.20), respectively. The HR of MetS for colon cancer across BMI categories was 1.12 (95% CI, 1.06 to 1.19), 1.14 (95% CI, 1.08 to 1.20), and 1.16 (95% CI, 1.12 to 1.21) in women with BMIs <23.0 kg/m2, 23.0-24.9 kg/m2, and ≥25.0 kg/m2, respectively. The HR of MetS for rectal cancer across corresponding BMI categories was 1.16 (95% CI, 1.06 to 1.26), 1.14 (95% CI, 1.05 to 1.23), and 1.13 (95% CI, 1.06 to 1.20). The heterogeneity of associations across BMI categories was not significant in either colon or rectal cancer (p=0.587 for colon cancer and p=0.927 for rectal cancer). Conclusions Women with MetS were at increased risk of colon and rectal cancer. Clinical and public health strategies should be considered for primary CRC prevention with an emphasis on improving women's metabolic health across all BMI groups.